2022
DOI: 10.1016/j.lfs.2022.120392
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic potential of regulatory T cells in reducing cardiovascular complications in patients with severe COVID-19

Abstract: The SARS coronavirus 2 (SARS CoV-2) causes Coronavirus Disease (COVID-19), is an emerging viral infection. SARS CoV-2 infects target cells by attaching to Angiotensin-Converting Enzyme (ACE2). SARS CoV-2 could cause cardiac damage in patients with severe COVID-19, as ACE2 is expressed in cardiac cells, including cardiomyocytes, pericytes, and fibroblasts, and coronavirus could directly infect these cells. Cardiovascular disorders are the most frequent comorbidity found in COVID-19 patients. Immune cells such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 164 publications
(255 reference statements)
0
4
0
Order By: Relevance
“…Adoptive transfer of Tregs has been shown to prevent the development of atherosclerosis and induce a shift in plaque composition toward a more stable phenotype 181 . This involves either isolating Tregs that have differentiated in vivo and expanding them ex vivo, or generating iTregs cells in vitro, and then transferring the Tregs/iTregs into the body 195 . The potential prevention of atherosclerosis may be achieved by the adoptive transfer of CD4 + CD25 + Tregs into ApoE −/− mice 182 .…”
Section: Targeting Tregs For the Prevention And Treatment Of Cvdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adoptive transfer of Tregs has been shown to prevent the development of atherosclerosis and induce a shift in plaque composition toward a more stable phenotype 181 . This involves either isolating Tregs that have differentiated in vivo and expanding them ex vivo, or generating iTregs cells in vitro, and then transferring the Tregs/iTregs into the body 195 . The potential prevention of atherosclerosis may be achieved by the adoptive transfer of CD4 + CD25 + Tregs into ApoE −/− mice 182 .…”
Section: Targeting Tregs For the Prevention And Treatment Of Cvdsmentioning
confidence: 99%
“…181 This involves either isolating Tregs that have differentiated in vivo and expanding them ex vivo, or generating iTregs cells in vitro, and then transferring the Tregs/iTregs into the body. 195 The potential prevention of atherosclerosis may be achieved by the adoptive transfer of CD4 + CD25 + Tregs into ApoE −/− mice. 182 Additionally, the therapeutic benefits of transferring Tregs into patients have been widely acknowledged.…”
Section: Adoptive Transfer Of Tregsmentioning
confidence: 99%
“…However, depending on the patient's underlying disease and the strength of the immune system, some of the symptoms would be different in the patients (8,9). Based on the studies and evidence, the stimulation of the immune system in COVID-19-infected patients can eventually lead to a cytokine storm (10). The inflammation caused by cytokine storms can damage the main organs in the patient's body (11).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have appreciated the role of Treg on SARS‐CoV‐2 infection [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. It has been found that Tregs in severe COVID‐19 patients display increased expression of PD‐1 and several disturbances in transcriptional signatures [ 29 ].…”
Section: Introductionmentioning
confidence: 99%